PWE-052 Current practices in ileal pouch surveillance for ulcerative colitis patients in three london ibd referral centres. (17th June 2017) - Samaan, MA; Segal, J; Kabir, M; Morgan, S; Forsyth, K; Elkady, S; Kok, K; Arenaza, AP; Seward, E; Vega, R; Caro, S Di; Mehta, S; et al.
Abstract : Introduction: There are no universally accepted guidelines regarding surveillance of IBD patients after ileal pouch-anal anastomosis (IPAA). The BSG suggest 'considering' pouchoscopy and biopsy but accepts 'there is no clear evidence that surveillance is beneficial and thus it cannot be strongly recommended'. We assessed how frequently pouch surveillance is carried out at our centres. We also evaluated the approaches used for pouchoscopy and the use of endoscopic biopsies. Method: The records of 177 patients who underwent IPAA for IBD at three London IBD referral centres (Guy's and St Thomas', University College London and St Mark's Hospitals) were reviewed. Patients with Crohn's or less than 1 year post-surgical follow-up, were excluded. Data regarding the endoscopic follow-up of the remaining 126 patients was collected retrospectively. Fisher's exact (categorical) and signed rank sum (continuous) tests were used. Results: 15/126 (12%) had never undergone pouchoscopy for any indication. Of the 111 who had, the median interval between pouch surgery and first pouchoscopy was 1.3 years (0.2–6.4). Median number of pouchoscopies was 3 (0–11), carried out at a median frequency of every 2.4 years (0.9–8.1). Two rectal cuff cancers were found. 59/126 (47%) had never undergone pouchoscopy with surveillance as the sole indication and no significant differences were found between sub-groups. Median pouch duration 7.1y surveillance, 8.4y none (p=0.193). Gastro, Surgery and joint-care surveillance rates: 7/16 (44%), 28/46 (61%) and 32/64 (50%), respectively (p=0.382). Pouchitis history surveillance rates: present 29/51 (57%), absent 36/73 (49%)(p=0.501). Rates of examination and biopsy by pouch region shown in fig 1. Conclusion: We demonstrated wide variation in endoscopic surveillance of UC-IPAA patients, even amongst experienced clinicians. Some patients underwent several pouchoscopies for surveillance, whereas others had none. In additional, the decision whether to perform surveillance pouchoscopy did not seem to be related to risk factors such as pouch duration. Moreover, endoscopic pouch assessments could be considered incomplete in a proportion of patients with no description of the prepouch ileum or rectal cuff/anal transition zone. Disclosure of Interest: None Declared